Epoxide formation from heterogeneous oxidation of benzo[a]pyrene with gas-phase ozone and indoor air. Issue 10 (29th August 2017) - Zhou, Shouming; Yeung, Leo W. Y.; Forbes, Matthew W.; Mabury, Scott; Abbatt, Jonathan P. D.
Abstract : This work demonstrates the production of mono- and diol-epoxides from heterogeneous oxidation of benzo[ a ]pyrene with gas-phase ozone. Abstract : The formation of two classes of epoxide products from the heterogeneous reaction of benzo[ a ]pyrene (BaP) with gas-phase ozone was demonstrated. BaP was coated on a Pyrex glass tube and oxidized with different concentrations of ozone. After oxidation, the epoxide products were derivatized by N -acetylcystein (NAC) and then analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The results show that in addition to mono-epoxides, diol-epoxides were also formed. BaP exposed to genuine indoor air also produces mono- and diol-epoxides, having similar chromatograms to those produced by oxidation of BaP by low concentrations of ozone. Although it is well recognized that diol-epoxides are formed from BaP oxidation in the human body and that they exhibit carcinogenicity via formation of adducts with DNA, this is the first demonstration that such classes of compounds can be formed by abiotic heterogeneous oxidation.